Seed mucilage-based advanced carrier systems for food and nutraceuticals: fabrication, formulation efficiency, recent advancement, challenges, and perspectives - Shishir, Mohammad Rezaul Islam; Suo, Hao; Taip, Farah Saleena; Ahmed, Maruf; Xiao, Jianbo; Wang, Mingfu; Chen, Feng; Cheng, Ka-Wing (Taylor & Francis Group, 2023)
Seed mucilages are potential sources of natural polysaccharides. They are biodegradable, biocompatible, sustainable, renewable, and safe for human consumption. Due to the desirable physicochemical and functional properties (e.g. gelling, thickening, stabilizing, and emulsifying), seed mucilages have attracted extensive attention from researchers for utilization as a promising material for the development of advanced carrier systems. Seed mucilages have been utilized as natural polymers to improve the properties of various carrier systems (e.g. complex coacervates, beads, nanofibers, and gels) and for the delivery of diverse hydrophilic and lipophilic compounds (e.g. vitamins, essential oils, antioxidants, probiotics, and antimicrobial agents) to achieve enhanced stability, bioavailability, bioactivity of the encapsulated molecules, and improved quality attributes of food products. This review highlights the recent progress in seed mucilage-based carrier systems for food and nutraceutical applications. The main contents include (1) sources, extraction methods, and physicochemical and functional characteristics of seed mucilages, (2) application of seed mucilages for the development of advanced carrier systems, (3) major issues associated with carrier fabrication, and (4) mechanisms of carrier development, latest improvements in carrier formulation, carrier efficiency in the delivery of bioactive agents, and application in food and nutraceuticals. Furthermore, major challenges and future perspectives of seed mucilage-based carriers for a commercial application are discussed.